2022
DOI: 10.1155/2022/6872542
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Teeth with an Advanced Lithium Disilicate Ceramic: A Case Report and 1-Year Follow-Up

Abstract: Advancements in materials science and bonding protocols as well as new manufacturing methods foster the development of novel ceramic materials to meet the increased demands for highly aesthetic, biocompatible, and long-lasting restorations in fixed prosthodontics. This case report highlights the minimally invasive rehabilitation with a new advanced lithium disilicate (ALD) ceramic block. It is reinforced with virgilite crystals in managing esthetic demand of patient besides having a high flexural strength. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In comparison to the other lithium disilicate glass ceramics, ALD ceramics showed higher hardness levels that could make them an attractive clinical choice for restorations in high-stress-bearing areas. Moreover, the chairside processing of ALD ceramics is simpler, quicker, and more practical than that of zirconia ceramics [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the other lithium disilicate glass ceramics, ALD ceramics showed higher hardness levels that could make them an attractive clinical choice for restorations in high-stress-bearing areas. Moreover, the chairside processing of ALD ceramics is simpler, quicker, and more practical than that of zirconia ceramics [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a shortened final firing cycle saves clinical time to complete its crystallization. 8 A previous study found that ALD presented superior hardness and surface smoothness compared with other evaluated glass ceramics. 2 It was also reported that ALD has a higher resistance to wear and presents similar fracture behavior compared with LD.…”
Section: Introductionmentioning
confidence: 94%
“…The time efficiency, predictability, and economically attractive treatment options are important aspects in CAD/CAM dentistry. CEREC's newly introduced advanced lithium disilicate ceramic produces an esthetically pleasing and clinically excellent restoration when used in conjunction with the chairside economical restoration of esthetic ceramics (Chairside EREC)/ceramic reconstruction (CEREC) system [20].…”
Section: Introductionmentioning
confidence: 99%
“…Besides having a high flexural strength, advanced lithium disilicate ceramic is reinforced with virgilite crystals in order to satisfy the esthetic demands of patients. A biaxial strength of more than 700 MPa is claimed by the manufacturer, along with improved optical properties with a remarkable sintering speed of approximately four minutes, which provides a shorter processing time and high flexural strength [20], thus, optimizing the chairside workflow. It is anticipated that new treatment options will be available for these advanced lithium disilicate ceramics.…”
Section: Introductionmentioning
confidence: 99%